Vancomycin and its crystalline degradation products released from bone grafts and different types of bone cement - Klapkova, Eva; Nescakova, Monika; Melichercik, Pavel; Jahoda, David; Dunovska, Katerina; Cepova, Jana; Prusa, Richard (Folia microbiologica, 2020)
Vancomycin is often used in orthopedic surgery as a local prophylaxis of bacterial infection. The aim of this work was to compare the release of vancomycin and its biologically inactive crystalline degradation products (CDP-1) during in vitro experiments from different types of local antibiotic delivery systems (bone grafts and bone cements). The concentrations of vancomycin and its crystalline degradation products were determined by high-performance liquid chromatography. Each experiment was performed in a phosphate buffer solution over 21 days. Morselized bone grafts, synthetic bone cements Palacos and Copal, and synthetic bone grafts were tested as local carriers of vancomycin. The highest concentration approximately 670 mg/L of vancomycin was released from synthetic bone grafts Actifuse. Even after 21 days, the concentration of vancomycin was still above the minimum inhibitory concentration (MIC). The maximum concentration of vancomycin released in two experiments with human bone grafts exceeded 600 mg/L during the first day and was still above MIC level 21 days later when the experiment was concluded. By comparing the synthetic bone cements Palacos and Copal, Copal had the average maximum concentration of only 32.4 mg/L and Palacos 35.7 mg/L. The concentration of vancomycin fell below the MIC for vancomycin-resistant Staphylococcus aureus (VRSA) on the seventh day with Palacos and the ninth day with Copal. This study showed the insufficient concentration of released vancomycin from synthetic bone cements at the end of the experiment. For improvement of local prophylaxis, it would be beneficial to increase the amount of vancomycin in bone cements.
Keywords: Chromatography, High Pressure Liquid; antibakteriální látky; vankomycin; Microbial Sensitivity Tests; Humans; transplantace kostí; lidé; Bone Cements; Methicillin-Resistant Staphylococcus aureus; Anti-Bacterial Agents; Vancomycin; kostní cementy; Bone Transplantation; methicilin rezistentní Staphylococcus aureus; mikrobiální testy citlivosti; vysokoúčinná kapalinová chromatografie